Antifungal edible coatings to reduce decay and maintain postharvest quality of citrus, plums, and pomegranates - Pérez-Gago, María B.; Taberner, Verònica; Palou, Lluís (Department of Agricultural Food and Environmental Sciences, Università Politecnica delle Marche, 2024)
Most of the fresh fruits are highly perishable and fungal postharvest diseases are among the main causes that contribute to fruit waste. Synthetic chemical fungicides are currently the main tool to control postharvest decay, but different health and environmental alerts have raised the need to find safe and eco-friendly alternatives. Among them, the development of edible coatings with antifungal activity (AECs) has been addressed in the StopMedWaste project to control decay and maintain fruit quality of citrus fruits, plums, and pomegranates during cold storage and shelf life.